PENGARUH INVESTASI DAN KONSUMSI TERHADAP PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI PENGOLAHAN DI KOTA KENDARI - Kadir, Kadir; Rahim, Manat; Suriadi, La Ode (JURNAL EKONOMI UHO, 2016)
The objective of this study is to examine the de terminants of labor absorption in manufacture sector at Kendari City. This study used panel data comprising 6 districts at Kendari City in the period 2009-2013 including fixed effect model. The results showed that investment have positive effect on employment, while consumption have negative effect. The higer of investment the lower labor absorption in manufactures industry. This imply, when investment increasing, manufactures sector is labor saving